2008
DOI: 10.1016/j.vaccine.2008.03.100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Tat vaccine regimens in Mauritian cynomolgus and Indian rhesus macaques: Influence of Mauritian MHC haplotypes on susceptibility/resistance to SHIV89.6P infection

Abstract: Protection afforded by HIV Tat-based vaccines has differed in Indian rhesus and Mauritian cynomolgus macaques. We evaluated native Tat and Ad-HIVtat priming/Tat-boosting regimens in both species. Both vaccines were immunogenic. Only the Ad-tat regimen modestly reduced acute viremia in rhesus macaques after SHIV 89.6P challenge. Confounding variables uncovered in Mauritian macaques included significant associations of susceptibility to infection with MHC class IB and class II H2 and H5 haplotypes, and resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 61 publications
6
40
0
Order By: Relevance
“…The unique natural history of these animals is manifest by exceptionally low genetic diversity. We have characterized the MHC genetics of this population and found only seven common haplotypes containing fewer than 30 MHC class I alleles (12,48). The three most common MHC haplotypes each express Mafa-A*25 and Mafa-A*29.…”
Section: Mafa-a*25 and Mafa-a*29 Restrict Cd8mentioning
confidence: 98%
“…The unique natural history of these animals is manifest by exceptionally low genetic diversity. We have characterized the MHC genetics of this population and found only seven common haplotypes containing fewer than 30 MHC class I alleles (12,48). The three most common MHC haplotypes each express Mafa-A*25 and Mafa-A*29.…”
Section: Mafa-a*25 and Mafa-a*29 Restrict Cd8mentioning
confidence: 98%
“…Although the reasons for these conflicting results are not known, it is likely that the different outcomes of infection may reflect species differences with regard to immunogenicity or host resistance factors; difference in vaccine characteristics; immunization protocol; timing and route of administration; delivery systems; and/or type, dose, and route of administration of the challenge virus. To this respect, a recent comparative study of the same vaccine regimens with biologically active Tat (86 aa) in cynomolgus and rhesus monkeys showed the association of identified MHC class I and class II haplotypes with control of plasma viremia after intravenous challenge of SHIV 89.6P and suggests that the difference in the challenge dose may also play a role in different infection outcomes [182,Cafaro et al,in preparation].…”
Section: Preclinical Studies With Hiv-1 Tat Vaccinesmentioning
confidence: 99%
“…Retrospective analysis of 22 macaques vaccinated with Tat or a Tat-expressing adenoviral vector revealed that monkeys with the H6 or H3 MHC class IB haplotype were overrepresented among aviremic or controller animals, whereas macaques with the H2 or H5 haplotype clustered in the noncontrollers (12). More recently, the H6 haplotype was reported to correlate with control of chronic infection with simian immunodeficiency virus (SIV) mac251, regardless of vaccination (18).…”
mentioning
confidence: 99%
“…Here, we performed a retrospective analysis of 112 Mauritian cynomolgus macaques, which included the 22 animals studied previously (12), to evaluate the impact of the challenge dose and class IB haplotype on the acquisition and severity of simian/human immunodeficiency virus (SHIV) 89.6P cy243 infection in 45 control monkeys and 67 monkeys vaccinated with Tat from different protocols ( Table 1).…”
mentioning
confidence: 99%